THE CRISTIADA IN ZAMORA AND ITS REGION: THE CASE OF PRIEST FRANCISCO ESQUIVEL, ALIAS CAPTAIN VILLALOBOS (Tzintzun, Revista de Estudios Históricos, 2022)
The trajectory of the Michoacan priest Francisco Esquivel is reviewed: fromseminarian to Cristero captain, and then to priest, based on two unpublishedautobiographical writings that increase the heritage of literature on the CristeroWar. We analyze the reasons that decided the seminarian to take up arms, as partof the centuries-long controversy in Christian thought about the legitimacy ofviolence.
Keywords: Cristiada in Michoacán; catholicism and legitimate violence; Church-State relations (20th century); cristero literature